17 Myocardial scar and association with long term outcomes in patients with cardiac devices. (28th January 2023) - Shabi, Mubien; Saunderson, Christopher D; Charlotte Cole, John Gierula; Paton, Maria; Brown, Louise A; Javed, Wasim; Sharrack, Noor; Levelt, Eylem; Dall'Armellina, Erica; Greenwood, John P; Plein, Sven; Witte, Klaus K; et al.
Abstract : Introduction: Long-term right ventricular (RV) pacing leads to heart failure or a decline in left ventricular (LV) function in up to a fifth of patients. 1 We aimed to establish whether the presence of focal left ventricular myocardial fibrosis detected by late gadolinium enhancement on cardiovascular magnetic resonance (CMR) is associated with long term adverse outcomes in patients with long term cardiac devices. Materials and Methods: Between February 2018 and March 2019, we prospectively recruited two cohorts1 : 1) Patients with high grade atrioventricular block who were planned to have a cardiac device implanted and anticipated to have a high burden of RV pacing (N=60) and 2) Patients with a cardiac device implanted in the prior 3 years with an RV pacing burden <5%. (N=42). All patients underwent CMR for the assessment of myocardial scar. Patients were followed up by review of electronic records and pacemaker checks until censoring for a composite endpoint of all-cause mortality, heart failure hospitalisation and new atrial fibrillation lasting >24 hours. Results: Myocardial scar was present in 53 (52%) patients. Over a median follow up of 2.9 years there were 46 MACE events in 38 patients (19 deaths, 13 heart failure hospitalisations, 14 atrial fibrillation episodes). On Cox regression analysis, age (HR 1.04, P=0.03), myocardial scar (HR 2.67, P=0.008), and LVEF (HR 0.95, P=0.04) were all associated with outcomes. RV pacing burden (%) was associated with outcomes in patients with myocardial scar (HR 1.01, P= 0.02) but not in those without scar (HR 1.00, P=0.91). In patients with scar, RV pacing burden >24% was associated with adverse outcomes Discussion: We have demonstrated that the presence of fibrosis is associated with adverse outcomes following RV pacing. Given that fibrosis can be identified before device implantation, it has a potential role in identifying those at risk of LV dysfunction and future heart failure, offering a potential selection criterion for an optimised pacing strategy. Conclusion: In patients with cardiac pacemakers, myocardial scar was associated with adverse outcomes. RV pacing burden was only associated with outcomes in those with scar. Reference: Christopher ED Saunderson, Maria F Paton, Louise AE Brown, John Gierula, Pei G Chew, Arka Das, Anshuman Sengupta, Thomas P Craven, Amrit Chowdhary, Aaron Koshy, Hazel White, Eylem Levelt, Erica Dall'Armellina, Pankaj Garg, Klaus K Witte, John P Greenwood, Sven Plein, Peter P Swoboda. Detrimental immediate- and medium-term clinical effects of right ventricular pacing in patients with myocardial fibrosis. Circulation: Cardiovascular Imaging . 2021;14 :e012256. Doi:10.1161/CIRCIMAGING.120.01225